Poverty and It’s Solution on Sunnah | الفقر والحلول للقضاء عليه فى ضوء السنة النبوية الشريفة - Zainul Muttaqin; Muhammad Nur Khozin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
This article discusses the problems of poverty and its solution in view of the hadith. Thisarticle will explore some hadith about poverty and how the prophet resolve theeconomic problems in the early Muslim community. This study is the literature, theauthor tries to analyze the prophet measures in the face of poverty. This article provesthat the Islamic religious community to give attention to the economic field.